PEMBINAAN KAMPANYE SOSIAL MELALUI PROGRAM A BETTER WORLD ACADEMY SEBAGAI BENTUK KEPEDULIAN TERHADAP SESAMA DI MASA PANDEMI COVID-19 - Afiyah, Nurul; Ruliani, Ruliani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
The Intership dan Certified Independent Study (MSIB) program is an initiative under Kampus Merdeka that provides students with opportunities to learn and develop themselves through activities outside the classroom. This program allows students to gain real-world experience in industries or professional fields for one to two semesters. This study employs a literature review method by analyzing relevant journal articles and integrating the author's firsthand experience in the MSIB program. This research focuses on the author's experience in the MSIB program at A Better World Academy (ABWA) for five months, from August 31, 2021, to January 31, 2022. After the training phase, ABWA students engaged in various social campaigns through the Campaign application, collaborating with organizations and communities working in social fields such as education, environment, health, and equality. The results show that a total of 57 challenges were successfully uploaded to the Campaign application, consisting of 19 environmental challenges, 20 educational challenges, 10 health-related challenges, and 8 equality-related challenges. The MSIB program has proven beneficial in helping students develop practical skills, raise social awareness, and expand their professional networks. This study aims to provide insights for other students interested in participating in similar programs to enhance their competencies and readiness for the workforce.